Sexual Dysfunction in Post-Episiotomy and Post-Cesarean Mothers - Queen Khoirun Nisa Mairo; Evi Yunita Nugrahini (Health Notions, 2017)
Background: According to the WHO, ''sexual health is a stable physical, emotional, mental and social wellbeing with regard to sexuality, and not merely the absence of disease, dysfunction or weakness. The objective of the study determined differences in sexual dysfunction between postpartum mother and episiotomy and post seksio cecarea. Method: This research use cross sectional method. The population in this study were all postpartum 6 months in RSUD Dr. M. Soewandhie Surabaya, with a total of 125 people. Instrument of data collection using questionnaire which have been made before. The questionnaire was adopted from the Consensus Development Conference on Female Sexual Dysfunction, the FSFI questionnaire. Statistical analysis using Chi Square test. Results and Analysis: The significance analysis on sexual function of both groups, overall in this study there was a statistically significant difference in the total FSFI score (p = 0.001), in which sexual dysfunction was categorized in total FSFI score ≤26.55. Discussion and Conclusion: It is concluded that there are significant differences in sexual function of women after vaginal delivery with episiotomy compared with post-cesarean. Sexual dysfunction should be on the agenda in the post-natal services, given that most women at that time had not started sexual activity. Keywords: Sexual dysfunction, Post-episiotomy, Post-Cecarean